2023
DOI: 10.3390/nano13142055
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Carboxylated Carbon Nanotubes@Expanded Graphite/Polyethersulfone Composite Bipolar Plates for PEM

Abstract: Composite bipolar plates (BPs) hinder their application in proton exchange membrane fuel cells (PEMFC) because of their poor conductivity and mechanical properties. Nanofillers can effectively solve this problem but often have a limited effect due to their easy agglomeration. In this work, a continuous mesh carboxylated multi-walled carbon nanotube (MWCNT) coating on the surface of graphite was synthesized by chemical vapor deposition (CVD) and carboxylation modification, and the composite BPs were prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…For the newnanofiller modification, 2023 Li [6] in synthesized a continuous reticulated carboxylated multi-walled carbon nanotube (MWCNT) coating on the surface of expanded graphite using chemical vapor deposition (CVD) and carboxylation modification, and prepared composite bipolar plates by moulding using reticulated carboxylated MWCNT, expanded graphite and resin. By optimising the carboxylation treatment time and nanofiller content, the composite bipolar plates had the best performance at a carboxylation treatment time of 15 min and a filler content of 2.4%.…”
Section: Study Of Composite Bipolar Plates With Expanded Graphite (Eg...mentioning
confidence: 99%
“…For the newnanofiller modification, 2023 Li [6] in synthesized a continuous reticulated carboxylated multi-walled carbon nanotube (MWCNT) coating on the surface of expanded graphite using chemical vapor deposition (CVD) and carboxylation modification, and prepared composite bipolar plates by moulding using reticulated carboxylated MWCNT, expanded graphite and resin. By optimising the carboxylation treatment time and nanofiller content, the composite bipolar plates had the best performance at a carboxylation treatment time of 15 min and a filler content of 2.4%.…”
Section: Study Of Composite Bipolar Plates With Expanded Graphite (Eg...mentioning
confidence: 99%
“…In addition, after the addition of MWCNTs, due to the presence of the conductive network, the conductivity of the composite bipolar plate containing 5 wt% MWCNTs and 35 wt% graphite was further reduced to 161.57 S /cm, with a flexural strength of 42.65 MPa and a corrosion current density of less than 1 μA/cm2 . Li et al [20] prepared reticulated carboxylated MWCNT, expanded graphite and resin were molded to prepare composite bipolar plates. The experimental results showed that when the carboxylation treatment time was 15 min and the filler content was 2.4%, the planar conductivity reached 243.52 S/cm and the flexural strength reached 61.9 MPa.Unlike the conventional composite bipolar plates with directly added MWCNTs, the carboxylated MWCNTs dispersed more homogeneously and the wettability with the resin was significantly improved.…”
Section: Carbon Nanotube Reinforced Compositesmentioning
confidence: 99%